Terra de quilombo em região metropolitana: impactos sociais na comunidade de Abacatal, Pará - SOUSA, Vânia Maria Carvalho de (2019)
This work is located in the context of Amazonia, specifically in the metropolitan region of Belém. It intends to discuss the effectiveness of power relations in a very conflictive context in the Quilombola community of Abacatal, 8 km away from the center of Ananindeua. The complexity is due to the use of land, not only by the residents, but also by national and multinational companies that have been interfering in the life of the community for some time. In speaking about the Quilombola community we are referring not only to the right of territoriality, which is a social right, but also contemplates the environmental rights that are overshadowed by great undertakings that hurt the existence of humankind as a whole. In this way, we will present fairly strong data on the impacts that are currently being caused in the community, coming from projects that are being considered and executed without prior consultation, such as the gas pipeline, the roadway, the Linhão and the Parana railroad.